Impurity and gender in the Hebrew Bible - Goldstein, Elizabeth W. (Lanham Boulder New York London Lexington Books, 2015)
Narratives, genealogy, and gender in P -- Gender and impurity in P -- Expanding the notion of purity: gender, blood, and the Holiness code -- Blame it on a metaphor: female degradation and blood in Ezekiel -- Gender and impurity in Ezra-Nehemiah -- NDH as sin in the Scrolls -- Impurity in the foundation of Jews and Judaism
Narratives, genealogy, and gender in PGender and impurity in P -- Expanding the notion of purity: gender, blood, and the Holiness code -- Blame it on a metaphor: female degradation and blood in Ezekiel -- Gender and impurity in Ezra-Nehemiah -- NDH as sin in the Scrolls -- Impurity in the foundation of Jews and Judaism.
Includes bibliographical references (pages 117-128) and indexes
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Dead Sea Scrolls; Women -- Biblical teaching; Women -- Religious aspects -- Judaism; Purity, Ritual -- Biblical teaching; Purity, Ritual -- Judaism -- History of doctrines; Hochschulschrift